Problem dan Tantangan Pengembangan Kurikulum Ma’had Aly di Indonesia - Aena, Nur (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
Ma'had Aly is an Islamic religious college that organizes academic education in the field of Islamic religious mastery based on the yellow book organized by Islamic boarding schools. Ma'had Aly was formed because it is believed to be able to make a better generation of ulama cadres who compete with the demands of society and the times. At the same time, society is growing rapidly so that changes that occur are not only in the field of technology but also in the field of socio-economics, science which requires every community to be able to think and deal with all changes that occur, one way is by doing innovation in all fields, especially in the field of education. In the field of education, one of them is by developing a curriculum. However, there are problems and challenges in developing the Ma'had Aly curriculum in Indonesia. From these problems, the authors are interested in studying the problems and challenges of developing the Ma'had Aly curriculum. In describing this study, the author uses the literature review method. The results of this study indicate that the problems and challenges that must be faced in developing the Ma'had Aly curriculum are the lower ability of new students from year to year which has an impact on the decline in the quality of graduates. In addition, there are two factors that become challenges in developing the Ma’had Aly curriculum. In internal factors come from power relations, curriculum problems, quality of human resources, and costs. While external factors include dichotomic, general knowledge, lack of spirit of inquiry, memorization, and certified oriented. By understanding the problems and challenges in developing the Ma'had Aly curriculum, it will make it easier for institutions to develop a more appropriate curriculum to produce the best generation.